Aerobic Exercise and Metabolic Syndrome: The Role of Sympathetic Activity and the Redox System - Monda, Vincenzo; Sessa, Francesco; Ruberto, Maria; Carotenuto, Marco; Marsala, Gabriella; Monda, Marcellino; Cambria, Maria Teresa; Astuto, Marinella; Distefano, Alfio; Messina, Giovanni (Diabetes, metabolic syndrome and obesity, 2020)
Aerobic exercise can greatly assist in reducing collateral effects of metabolic syndrome (MetS). Moreover, aerobic exercise is associated with sympathetic activation and adaptive responses to sustain muscle engagement, changes in the release of Orexin A, a pleiotropic neuropeptide. The aim of this study was to analyze the beneficial effects of aerobic exercise without dietary changes, in a cohort of MetS subjects, focusing on the role of sympathetic and orexinergic activity. Several blood parameters linked to MetS ROS production, heart rate, galvanic skin response, d-ROM test, and Orexin A serum levels were evaluated in ten males with MetS (BMI 30-34.9) before and after a period of 6 months of aerobic exercise compared to ten healthy subjects. Ten male subjects (aged 54 ± 4.16) with MetS (MetS group) and ten healthy males (aged 49.7 ± 2.79, Healthy group) were told about the study protocol and possible risks, signed the informed consent, and voluntarily participated in the study. Several blood parameters were evaluated in the two tested groups and were re-evaluated in the MetS group after 6 months of training (MetS6M group). The training protocol consisted of more than 30 min/day of walking (average speed of 4.5 km/h) and 3 days/week of aerobic activities (jogging under heart rate control - 120-140 bpm for 45 min). The results showed that exercise induced a significant increase in GSR and plasma Orexin A but no significant increase in d-ROM values. Significant decreases in the serum ALT enzyme, triglycerides, and total cholesterol were found, while the HDL levels were significantly higher. Finally, a significant reduction of BMI and resting HR were reported. The results of this study confirm that physical activity is associated with sympathetic activation, having a pivotal role against adverse effects linked to MetS. Moreover, this study demonstrates that, in patients with MetS, Orexin A is involved in hormonal adaptations to exercise.